Case Report: Contiguous presentation of anti-MDA5 juvenile dermatomyositis and anti-AQP4 neuromyelitis optica spectrum disorder in an adolescent patient - Rebecca E. Wiersma; Zachary R. Shaheen; Colleen K. Correll; Patricia M. Hobday (Frontiers in Pediatrics, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare inflammatory disorder of the central nervous system (CNS) that is known to be associated with other neurologic and organ-specific autoimmune conditions. There has been increasing recognition of the association between NMOSD and systemic autoimmune disease, most commonly systemic lupus erythematosus and Sjogren's syndrome. We report a case of an adolescent presenting with anti-melanoma differentiation-associated protein 5 juvenile dermatomyositis (anti-MDA5 JDM) and NMOSD, exhibiting clinical features of myelitis, polyarthritis, myositis, and skin involvement. Currently, only two other published cases have described NMOSD associated with anti-MDA5 dermatomyositis, both in adults. To the best of our knowledge, this is the first reported case in an adolescent patient.